PENGEMBANGAN FORMULA ENTERAL PUTELA BERBASIS PUTIH TELUR (Albumen) DAN TEPUNG LABU KUNING (Curcubita Moschata) UNTUK PENDERITA DIABETES MELITUS - Fattonah, Anissa; Isdiany, Nitta (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2023)
This study aims to determine the effect of differences in egg white flour and pumpkin flour formulations on the quality of high-protein and high-fiber enteral food for Diabetes mellitus patients "PUTELA" including nutritional content, organoleptic properties, flowability, viscosity and shelf life. This type of research is an experimental design. Observations made include hedonic tests using 30 fairly trained panelists. The selected enteral formula is formula 3 with a ratio of egg white flour and pumpkin flour formulations of 60%:40% with an average rating of 5.3. Based on the Kruskall Wallis test on the aspects of taste, aroma, and consistency, there are differences between formulas 1, 2 and 3 indicated by a p-value <α 0.05. While in the aspects of color and consistency there is no difference between formulas 1, 2 and 3 indicated by a p-value> α 0.05. In this study, it meets the requirements of being fairly high in protein for every 100 kcal containing 4.5 grams of protein. The cost of the putela formula per recipe is Rp. 26,664,- and per serving Rp. 6,666,-. The suggestion in this study is that the use of not too ripe bananas will increase the success of making banana flour.